Wild socialism : workers councils in revolutionary Berlin, 1918-21 - Comack, Martin (University Press of America, 2012)
Wild Socialism examines the rise, development, and decline of revolutionary councils of industrial workers in Berlin at the end of the First World War. This popular movement spread throughout Germany, and was without precedent in either the theory or practice of the Social Democratic party and allied trade unions.